Early and late diagnoses of 17β‐Hydroxysteroid dehydrogenase type‐3 deficiency in two unrelated patients. (14th February 2021) - Manyas, Hayrullah; Eroğlu Filibeli, Berna; Ayrancı, İlkay; Güvenç, Merve S.; Dündar, Bumin N.; Çatlı, Gönül
Abstract: 17β‐hydroxysteroid dehydrogenase type 3 deficiency is a rare cause of 46 XY disorders of sexual development. Mutations in the  HSD17B3  gene result in reduced activity of the 17β‐HSD3 enzyme, decreasing the conversion of androstenedione to testosterone. In this report, two cases, admitted with different clinical findings in the neonatal and adolescent periods and were decided to be raised in different genders are presented. The first case who had complete female external genitalia presented on the third postnatal day with the complaint of swelling in the groin. He was decided to be raised as a male and was treated successfully with parenteral testosterone in order to increase phallus size before surgical correction of the external genitalia. The second case was an adolescent girl who presented due to pubertal virilisation and primary amenorrhoea and chose female gender. Molecular genetic analyses of the  HSD17B3  gene revealed two different previously reported homozygous variants. We emphasise that patients with 17β‐hydroxysteroid dehydrogenase type 3 deficiency can present with heterogeneous clinical findings in different age groups. Early diagnosis is important to prevent future gender confusion and related problems.